(untitled) (International Journal of Technology and Management Research, 2021)
An ab initio density functional theory (DFT) is employed to explore the effect of adsorption of SO2 and H2S gases on gold-doped small diameter (5,0) zig-zag single-walled carbon nanotubes. Au-SWCNT nanostructures are extremely sensitive to the presence of both SO2 and H2S gases. Charge is transferred from the Au-SWCNT to the SO2 upon the adsorption of the gas molecules onto the Au-SWCNTs surface. There is a decrease in the energy bandgap of the Au-SWCNT. As a consequence, the electrical conductivity of Au-SWCNTs/SO2 is extremely enhanced. On the contrary, the adsorption of H2S gas onto the surface of the gold-doped nanotube provokes charge transfer from H2S to the Au-SWCNT. Another interesting observation is that the energy bandgap of AuSWCNT increases upon the adsorption of the H2S gas molecules onto the Au-SWCNT surface, thereby decreasing the electrical conductivity of the Au-SWCNT/H2S nanostructure. Citation: Elloh, V. W., Boadu, E. O., Ofosuhene, D. F. and Arhin, I. (2021). Computational Modelling of SO2 and H2S gas interacting with small diameter Au-doped (5, 0) zig-zag single-walled carbon nanotubes. International Journal of Technology and Management Research (IJTMR), Vol. 6 (2): Pp.87-95. Received: March 20, 2021 Accepted: September 1, 2021